Using TeleCatch to investigate human mobility discourses in the African Telegram sphere - Carneiro, Bia; Tucci, Giulia (2024)
This working paper employs the open-source TeleCatch tool to investigate the presence of content related to migration/human mobility on Telegram messages exchanged in Africa-based groups and channels. The goal was to generate data to examine human mobility narratives in the context of the African continent, including how people in Africa talk about migration and displacement, how migration and displacement in Africa are perceived by outsiders, and if/how channels with information on human mobility shape actual mobility patterns.